Low Health Literacy Is Associated with Increased Transitional Care Needs in Hospitalized Patients. Issue 11 (20th September 2017) - Boyle, Joseph; Speroff, Theodore; Worley, Katherine; Cao, Aize; Goggins, Kathryn; Dittus, Robert S.; Kripalani, Sunil
Abstract : BACKGROUND: In discharge planning, a patient needs assessment helps to identify risk factors that should be addressed to promote a safe and effective transition in care. Low health literacy is associated with worse postdischarge outcomes, but little research has examined its relation to other addressable risk factors. OBJECTIVE: To examine the association of health literacy with the number and type of transitional care needs (TCN) among patients being discharged to home. DESIGN, SETTING, PARTICIPANTS: A cross‐sectional analysis of patients admitted to an academic medical center. MEASUREMENTS: Nurses administered the Brief Health Literacy Screen and documented TCNs along 10 domains: caregiver support, transportation, healthcare utilization, high‐risk medical comorbidities, medication management, medical devices, functional status, mental health comorbidities, communication, and financial resources. RESULTS: Among the 384 patients analyzed, 113 (29%) had inadequate health literacy. Patients with inadequate health literacy had needs in more TCN domains (mean = 5.29 vs 4.36; P < 0.001). In unadjusted analysis, patients with inadequate health literacy were significantly more likely to have TCNs in 7 out of the 10 domains. In multivariate analyses, inadequate health literacy remained significantly associated with inadequate caregiver support (odds ratio [OR], 2.61; 95% confidence interval [CI], 1.37‐4.99) and transportation barriers (OR, 1.69; 95% CI, 1.04‐2.76). CONCLUSIONS: Among hospitalized patients, inadequate health literacy is prevalent and independently associated with other needs that place patients at a higher risk of adverse outcomes, such as hospital readmission. Screening for inadequate health literacy and associated needs may enable hospitals to address these barriers and improve postdischarge outcomes.